Fostering active aging in older adults: results of a communication and social skills program - Mohammad Hossein Khajehpour; Shahla Ayoubi-Mahani; Hilda Mohammad-Rezakhani; Jamileh Farokhzadian (BMC Geriatrics)
Abstract Background Active aging empowers older adults to maintain physical, social, and psychological well-being as they age, enabling them to participate in social activities according to their preferences and capabilities. However, many older adults face communication and social skills challenges, necessitating interventions to minimize social communication barriers and promote active aging. Despite the importance of communication and social skills in active aging, further studies are essential to explore older adults’ perspectives and develop strategies that support active aging and address potential barriers. Therefore, this study aimed to investigate the effect of communication and social skills training on the active aging of older adults. Methods This quasi-experimental trial with randomized allocation study involved 80 older adults from two daycare centers in southeastern Iran in 2024. Participants were randomly assigned to either a control or an intervention group. The intervention group received an eight-session communication and social skills training program, conducted twice a week for two hours in groups of 20. Both groups completed the Iranian Active Aging Measurement Instrument before and one month after the intervention. Results The mean ages of participants in the intervention and control groups were 68.94 ± 7.27 and 67.13 ± 5.09 years, respectively. Training in communication and social skills led to a significant increase in the total score of active aging (98.18 ± 17.77) and its dimensions (mindfulness, active insight, physical-functional dynamics, interactionism, role-playing, and social participation) during the post-test stage compared to the pre-test (148.97 ± 13.19), (t = -25.87, p < 0.001) and the control group (1.101 ± 8.18), (t = 1.35, p = 0.18). Conclusion This study contributes valuable evidence supporting psychosocial interventions for active aging. To advance this field, further research should focus on the long-term impact, cultural adaptability, and multimodal strategies that comprehensively address physical, cognitive, and social domains.